Preliminary results of the shape analysis of pine processionary moth scales in Turkey - Kahraman İPEKDAL; Zeycan HELVACI; Selim ÇAĞLAR (Turkish Journal of Forestry, 2016)
Larvae of the two pine processionary moth (PPM) sister species, Thaumetopoea wilkinsoni and T. pityocampa, causes severe allergies in mammals and are dangerous defoliators of Mediterranean pines. While T. pityocampa occurs mainly in Europe, T. wilkinsoni occurs in Turkey and the Middle East. Recent studies showed that ranges of the two species are in contact in Turkey. Female moths of the two species cover their eggs with scales on their abdomens. These scales are believed to protect eggs from parasitism. Although T. wilkinsoni and T. pityocampa exhibit highly similar morphologies, few studies have suggested that scale morphology could be used for species identification. However, our field observations in Turkey do not confirm this suggestion. Nevertheless, statistical approaches have never been used on this issue. In this study, we aimed at solving this contradiction by digitizing PPM scale shape photographs taken standardly from 60 individuals collected from different locations in Turkey and Cyprus and by subjecting them to geometric morphometry approaches. We conducted shape analysis by using TPS software and Elliptic Fourier Outline Analysis which is a sensitive method for morphometric computations. Results did not reveal any correlation between scale morphology and species taxonomy. This result could be interpreted as an insufficiency of scale morphology being able to be used as a taxonomic character to separate T. wilkinsoni and T. pityocampa in Turkey. However, it should be kept in mind that these two species have a contact zone in Turkey, which might cause hybridization. This phenomenon could completely change morphological patterns. In order to reach more accurate results, this study should be repeated with samples from the entire ranges of the two species.